7D.08: DETECTING HYPERTENSIVE RETINOPATHY USING RETINAL VASCULAR GEOMETRY. (June 2015) - Triantafyllou, A.; Al-Diri, B.; Anyfanti, P.; Hunter, A.; Douma, S.
Abstract : Objective: Identification of subtle vascular alterations of the retina may serve as an early index of hypertension-induced target organ damage, in terms of global cardiovascular risk assessment. Evaluation of retinal vessels can be achieved promptly, easily and non-invasively using the non-mydriatic fundus camera; as such, the need to identify new, reliable, and easily estimated cardiovascular risk markers derived from the retinal vasculature is growing rapidly. Apart from the retinal vascular diameters, research has recently focused on the evaluation and the quantitative estimation of other signs of retinal vascular geometry, such as the bifurcation of the retinal vessels. Design and method: We studied naïve, never-treated patients with recent duration of hypertension, confirmed with 24-hour ambulatory blood pressure (BP) and a control group consisting of healthy volunteers. All patients underwent fundus photography with a non mydriatic NIDEK AFC-230/210 camera. Innovative software was developed to estimate retinal vascular geometry, using novel advances in retinal digital image analysis which allow precise measurements of features of the whole vascular network spread across the retina. The retinal bifurcation geometry was expressed with the asymmetry ratio (α), area ratio (β) and the bifurcation index (λ). Results: In total 69 participants, 48 hypertensives and 21 matched normotensives were included in this pilot collaborative study. Hypertensives exhibited all measured tortuosity indices significantly increased (α: 0.674 vs 0.624, p = 0.001, β: 1.480 vs 1.431, p = 0.008 and λ:0.804 vs 0.771, p = 0.001 respectively). Correlations between the above parameters and the components of office and ambulatory BP are depicted in table 1. The strongest correlation was found with office systolic BP, followed by the nighttime systolic measurements. Figure. No caption available. Conclusions: This is the first study showing that even in "naïve" hypertensive patients, all tortuosity indices, estimated by innovative software, were increased compared to normotensive controls. All studied tortuosity indices were significantly associated with both office and 24-hour ambulatory BP. The verification of these promising novel indices of retinal vascular geometry in terms of cardiovascular disease prediction should be the subject of future studies.